CAMPUR KODE PADA ACARA PENDOPO KANG TEDJO DI TELEVISI REPUBLIK INDONESIA YOGYAKARTA - Deni Sukandar; Nusarini Nusarini (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to describe the form of code mixing, the meaning of code mixing, and code mixing functions at the Kang Tedjo Pendopo program on TVRI Yogyakarta. This research is a qualitative descriptive study. The analytical method is in the form of a translational matching method and a separate method. Methods presented informally. The results of this study were (1) The form of code mixing at the Pendopo Kang Tejo. (2) Meaning of code mixing at the Pendopo Kang Tejo program. (3) Functions mixed code at the Pendopo Kang Tedjo.